Endurance and transformation in Le Corbusier’s Redent - González Cubero, Josefina (Journal of Architecture and Urbanism, 2016)
The redent is the only generic building of Le Corbusier’s to endure and be transformed over the years between the initial and last designs, while others (immeubles-villas, gratteciel cartésien cruciforme, etc) disappeared altogether and still others arose during his lifespan (Unités, gratteciel «patte de poule» or “y”, etc). The residential redents’s obsessive presence can be attributed to its versatility in composition given that it is both open and closed at the same time. While the open form pools from French military architecture, the French garden, and social reformism, the closed form is highly attributed to Sitte’s tradition. To discover its phy- logeny rather than its achievements, all one needs to do is go back in time from the stale mechanism used in Hauptstadt-Berlin to the incipient form that was inoculated based on Fröbel’s teaching system of learning through play.